2013
DOI: 10.20533/ijrfidsc.2046.3715.2013.0012
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Generic Relay Attack on Contactless Transactions by Using NFC Mobile Phones

Abstract: Contactless technology is widely used in security sensitive applications, including identification, payment and access-control systems. Near Field Communication (NFC) is a short-range contactless technology allowing mobile devices to act primarily as either a reader or a token. Relay attacks exploit the assumption that a contactless token within communication range is in close proximity, by placing a proxy-token in range of a contactless reader and relaying communication over a greater distance to a proxy-read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 26 publications
(36 reference statements)
0
48
0
Order By: Relevance
“…A number of generic NFC relay attacks have been proposed in the literature [17,16]. Furthermore, successful relay attacks on payWave have been reported in, for example, [11].…”
Section: Relay Attacks Against Emv Contactless Smart Cardsmentioning
confidence: 99%
“…A number of generic NFC relay attacks have been proposed in the literature [17,16]. Furthermore, successful relay attacks on payWave have been reported in, for example, [11].…”
Section: Relay Attacks Against Emv Contactless Smart Cardsmentioning
confidence: 99%
“…In this case, the attacker intercepts a message sent to the victim and responds to the sender, pretending to be the intended receiver (Haselsteiner and Breitfuß, 2006;Roland, 2013;Sportiello, 2013;Francis et al, 2011).…”
Section: Relay Attackmentioning
confidence: 99%
“…Practical implementations of the mafia fraud attack have been proposed against contact and contactless based technologies [6,12,13,14,15]. Drimer and Murdoch [6] developed a relay attack against modern Chip-and-PIN system, while Francis et al [12] demonstrated an NFC peer-to-peer relay attack on smartphones, showing the simplicity of such attacks using off-the-shelf equipment.…”
Section: Introductionmentioning
confidence: 99%